2009
DOI: 10.1002/dvg.20466
|View full text |Cite
|
Sign up to set email alerts
|

Absence of TGFβ signaling in embryonic vascular smooth muscle leads to reduced lysyl oxidase expression, impaired elastogenesis, and aneurysm

Abstract: To address the requirement for TGFbeta signaling in the formation and maintenance of the vascular matrix, we employed lineage-specific mutation of the type II TGFbeta receptor gene (Tgfbr2) in vascular smooth muscle precursors in mice. In both neural crest- and mesoderm-derived smooth muscle, absence of TGFbeta receptor function resulted in a poorly organized vascular elastic matrix in late-stage embryos which was prone to dilation and aneurysm. This defect represents a failure to initiate formation of the ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 28 publications
5
70
0
Order By: Relevance
“…Consistent with this observation, conditional ablation of the Tgfbr2 gene in vascular SMCs recapitulated many of the features observed in Mkl2 -/-embryos, including aneurysmal dilation and dissection of the aorta during late embryonic development (Choudhary et al, 2009). However, these conclusions conflict with the observation that individuals with Marfan syndrome and Loeys-Dietz syndrome exhibit activation of TGF signaling and gain of TGF function in the arterial wall (Pearson et al, 2008).…”
Section: Research Articlesupporting
confidence: 69%
See 1 more Smart Citation
“…Consistent with this observation, conditional ablation of the Tgfbr2 gene in vascular SMCs recapitulated many of the features observed in Mkl2 -/-embryos, including aneurysmal dilation and dissection of the aorta during late embryonic development (Choudhary et al, 2009). However, these conclusions conflict with the observation that individuals with Marfan syndrome and Loeys-Dietz syndrome exhibit activation of TGF signaling and gain of TGF function in the arterial wall (Pearson et al, 2008).…”
Section: Research Articlesupporting
confidence: 69%
“…Genetic studies in mice and humans have shown that disruption of TGF signaling pathways results in defects in vasculogenesis and angiogenesis that are attributable, at least in part, to vascular SMCs (Pardali et al, 2010). Mice in which the Tgbr2 gene was conditionally ablated in vascular SMC precursors display arterial dilation and aneurysm formation, which leads to late embryonic lethality (Choudhary et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless, hypotheses such as this are now directly testable using our mouse model of the human mutation. More generally, beyond individuals with TAAD caused by LOX mutations, there is evidence that LOX may also play a role in modifying other forms of TAAD (32)(33)(34), which suggests that therapeutic manipulation of LOX activity may prove beneficial in other inherited aortopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal or perinatal ablation of TGF-b signaling in mouse models by deletion of Tgfbr2 in VSMCs with a VSMC-specific Cre (Langlois et al 2010), neural crest-and mesoderm-specific Cre (Choudhary et al 2009), or an inducible VSMC-specific Cre (Li et al 2014) results in defective elastogenesis, vessel wall dilation, aneurysm, and dissection. However, deletion of Tgfbr2 in VSMCs after 8 weeks of age has no apparent consequence on VSMC function and vessel wall homeostasis (Li et al 2014), suggesting that complete loss of TGF-b signaling in adult VSMCs does not cause major pathology in the adult vessel wall.…”
Section: Tgf-b Signaling In Vascular Homeostasismentioning
confidence: 99%